2013
DOI: 10.7314/apjcp.2013.14.10.5883
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Semaphorin4D Indicates Poor Prognosis and Prompts Monocyte Differentiation toward M2 Macrophages in Epithelial Ovarian Cancer

Abstract: Previously, we demonstrated overexpression of semaphorin4D (SEMA4D, CD100) to be closely related to tumor angiogenesis in epithelial ovarian cancers (EOCs). However, the function and expression of SEMA4D in the EOC microenvironment has yet to be clarified in detail. In this study, we confirmed that overexpression of SEMA4D in primary tumors and ascites was related to low differentiation, platinum resistance and a refractory status (P<0.05), while high M2 macrophage count and percentage were evident in EOC pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“… 1 11 It was reported that tumors that overexpress Sema4D are highly aggressive with poor prognosis and not easy to control during treatment. 1 , 7 , 12 , 13 Emerging evidence indicates that Sema4D might promote tumor growth and angiogenesis. 8 , 9 , 14 , 15 On the other hand, small GTPase Ras homolog (Rho) proteins, including RhoA, are highly expressed in human cancers.…”
Section: Introductionmentioning
confidence: 99%
“… 1 11 It was reported that tumors that overexpress Sema4D are highly aggressive with poor prognosis and not easy to control during treatment. 1 , 7 , 12 , 13 Emerging evidence indicates that Sema4D might promote tumor growth and angiogenesis. 8 , 9 , 14 , 15 On the other hand, small GTPase Ras homolog (Rho) proteins, including RhoA, are highly expressed in human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Sema4D enhances the recruitment of monocytes and promotes the differentiation of monocytes toward the M2 phenotype of macrophages, and in ovarian cancer is a marker of poor prognosis. 231 In another study it was observed that inhibitory sema4D antibodies enhance the recruitment of activated monocytes and lymphocytes into tumors in murine Colon26 and ErbB2…”
mentioning
confidence: 98%
“…Activates NF-KappaB and IL-8 to promote a pro-angiogenic response in endothelial cells 77 Promotes growth and invasion in HeLa cells 164 Promotes perineural invasion in a RhoA/ROK-dependent manner 80 Overexpression is related to poor prognosis in ovarian cancer 165 Suppresses c-Met activation and migration and promotes melanocyte survival 166 Cooperates with VEGF to promote angiogenesis and tumor progression 79 Over expression as a poor prognosis marker in ovarian cancer and promotes monocyte differentiation towards M2 macrophage 167 Promotes proliferation, migration and invasion in lung cancer cells 168 Recruits pericyte and regulates vascular permeability through endothelial production of PDGF-B and ANGPLT4 71 Promotes osteosarcoma development and metastasis 72 Blocking Sema4D with monoclonal anti Sema4D antibody promotes immune infiltration into tumor and enhances response to various other immunomodulatory therapies 85 Induction of expansion of myeloid derived suppressor cells by Sema4D derived from Head and Neck Squamous Cell Carcinoma 169…”
Section: Sema4dmentioning
confidence: 98%